Diversidade e bioprospecção de fungos endofíticos associados à Carapa guianensis Aublet (Andiroba) - Mariana Costa Ferreira (2013)
Endophytic microorganisms, those that asymptomatically reside within the plant tissue for at least one period of its life cycle, are capable of producing different bioactive metabolites of interest in medicine and agriculture. The species Carapa guianensis Aublet (Meliaceae), popularly known as Andiroba, is widely used in folk medicine. However, despite its ethnobotany use, few studies have been conducted in order to know the community of endophytic fungi associated with leaves of C. guianensis. The objective of this study was to characterize the diversity of the community of endophytic fungi associated with C. guianensis and evaluate it as a source of bioactive metabolites. Fragments of leaves were superficially disinfected and inoculated in Potato Dextrose Agar culture (BDA), Malt Extract Agar and Yeast Extract (YM) for isolation of endophytic fungi. The plates were incubated for 60 days and the obtained fungi were isolated and purified in PDA. All fungi obtained were preserved and deposited in the Collection of Micro-organisms and cells of the Federal University of Minas Gerais. After purification, 209 isolates of filamentous fungi were obtained, which were grouped using morphological and molecular Its characteristics into 42 morphospecies. The identification of the fungi was performed by sequencing the internal transcribed region (ITS1, ITS2-5.8S) rRNA gene and partial sequencing of the gene for β-tubulin and / or elongation factor 1 alpha (EF-1α). All taxa identified were classified as belonging to the phylum Ascomycota. The class Sordariomycetes was predominant, representing 91% of taxa obtained. Classes Dothideomycetes (6%) and Eurotiomycetes (3%) were also found. In the class Sordariomycetes were found species of the genera Colletotrichum, Diaporthe, Entonaema, Fusarium, Glomerella, Hypocrea, Menisporopsis, Pestalotiopsis, Phomopsis, Pilidiella and Xylaria. Among Dothideomycetes were identified species of the genera Botryosphaeria, Endomelanconiopsis and Guignardia. The genera belonging to the class Eurotiomycetes included species of Aspergillus and Penicillium. In comparison to other communities of endophytic fungi, the community associated with C. guianensis showed high diversity (Fisher-α = 17.23) and low dominance (Simpson = 0.93), indicating that the taxa found are homogeneously distributed in the community. Moreover, the fungal community showed moderate species richness (Margalef = 7.9). All endophytes obtained were cultured in PDA for 15 days and had its metabolites extracted with ethanol PA. The extracts were evaluated for antimicrobial activity and trypanocidal method microdilution plate. Extracts of the fungus Colletotrichum sp. UFMGCB 4991 and 4872, and Pilidiella cf. quercicola UFMGCB 4904 showed antibacterial activity against Escherichia coli with percentages of inhibition of 95, 98 and 99% at a concentration of 250 mg/mL, respectively. The extracts of fungi UFMGCB 4865, Endomelanconiopsis endophytica UFMGCB 4995 and Phomopsis sp. UFMGCB 4830 showed trypanocidal activity at 20 mg/mL with inhibition percentage of 77.8, 85.9 and 100%, respectively. Among the fungi that exhibited antimicrobial activity, the isolate Colletotrichum sp. UFMGCB 4991 was selected for testing fermentation, in order to improve its production of bioactive metabolites. Nutritional differences (type of culture medium) and temperature variation and growth time were assessed, totaling 64 different growing conditions. Extracts of Colletotrichum sp. UFMGCB 4991 underwent screening against all micro-organisms targets. Among the different conditions analyzed, 27 (42.18%) extracts showed activity against at least one of the micro-organisms targets. Furthermore, the extract of Colletotrichum sp. UFMGCB 4991 that initially was only able to inhibit Escherichia coli, following variations in the parameters of cultivation, demonstrated activity against Staphylococcus aureus, Candida albicans, Candida krusei and Cladosporium sphaerosperum. The results obtained in this study contribute to the knowledge about the community of endophytic fungi associated with Brazilian medicinal plants. Although the leaves of C. guianensis not having a large reservoir of endophytic fungi promising for bioprospecting studies, it was possible to detect two species (Pilidiella cf. quercicola and Endomelanconiopsis endophytica) first reported as producers of bioactive metabolites. The extracts produced by these fungi and those obtained by the fermentation test proved to be promising, these molecules may contain prototype for the development of new drugs.